(untitled) (Revista de Biología Marina y Oceanografía, 2022)
Most shark records are reported using different types of measurements; thus, length-to-length conversion parameters are needed to standardize and compare the available data as a function of different size measures. Shark biological information collected in the Mexican Pacific Northwest between 2006 and 2019 was used to estimate total fork length/precaudal length relationships for nine shark species. A total of 95,814 specimens were analyzed for length estimates, and a simple linear regression described all relationships correctly with a strong positive relationship (r > 0.80). The use of the present equations will allow more reliable population comparisons based on shark size.